2012
DOI: 10.2169/internalmedicine.51.6813
|View full text |Cite
|
Sign up to set email alerts
|

<sup>18</sup>F-FDG PET/CT Useful for the Early Detection of Rapidly Progressive Fatal Interstitial Lung Disease in Dermatomyositis

Abstract: Interstitial lung disease (ILD) frequently accompanies polymyositis (PM) and dermatomyositis (DM) and is a major cause of mortality. The rapid diagnosis of ILD is paramount. However, the early changes of presymptomatic ILD are difficult to detect. We present a patient with DM who had positive uptake in the lung of FDG-PET/CT as well as 'mechanic's hands' appearance, increased serum ferritin and serum anti-CADM-140 antibody, all before the detection of ILD by CT. Although aggressive treatment was initiated, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(11 citation statements)
references
References 23 publications
(21 reference statements)
0
11
0
Order By: Relevance
“…Furthermore, the FDG uptake is also observed in inflammatory cells. Morita et al 11 reported the usefulness of FDG-PET/CT for the detection of early inflammation in ILD in patients with DM. 6,22,23 Regarding the ILD, several studies reported the usefulness of FDG-PET/CT for the detection of ILD in DM patients.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Furthermore, the FDG uptake is also observed in inflammatory cells. Morita et al 11 reported the usefulness of FDG-PET/CT for the detection of early inflammation in ILD in patients with DM. 6,22,23 Regarding the ILD, several studies reported the usefulness of FDG-PET/CT for the detection of ILD in DM patients.…”
Section: Discussionmentioning
confidence: 99%
“…6,22,23 Regarding the ILD, several studies reported the usefulness of FDG-PET/CT for the detection of ILD in DM patients. Morita et al 11 reported the usefulness of FDG-PET/CT for the detection of early inflammation in ILD in patients with DM. Uehara et al 24 reported that FDG-PET/CT procedure sensitively illustrated active ILD lesions in connective tissue diseases, including DM.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In a case report, 18F-FDG PET/CT was used to screen for malignancy in a patient with clinically amyopathic dermatomyositis (CADM), and this showed 18F-FDG being distributed peripherally in both lungs, despite the absence of ILD on HRCT and normal arterial blood gases 53 . Despite aggressive immunosuppression, the patient later developed rapidly progressive ILD and died.…”
Section: Clinical Manifestations Of Ra-ildmentioning
confidence: 99%